Removal of reactive black 5 from textile wastewater by ozone and photo-fenton influence of industrial matrix effects - Hanela, Sergio (2020)
Fil: Hanela, S. Ministerio de Economía. Secretaría de Obras Públicas. Instituto Nacional del Agua. Subgerencia Laboratorio de Calidad de Aguas; Argentina. Ministerio de Capital Humano. Secretaría de Educación. Universidad de Buenos Aires. Departamento de Ingeniería Química; Argentina.